2022
DOI: 10.3389/fmicb.2022.823208
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-Transmitted Drug Resistance and Transmission Clusters in Newly Diagnosed Patients in Portugal Between 2014 and 2019

Abstract: ObjectiveTo describe and analyze transmitted drug resistance (TDR) between 2014 and 2019 in newly infected patients with HIV-1 in Portugal and to characterize its transmission networks.MethodsClinical, socioepidemiological, and risk behavior data were collected from 820 newly diagnosed patients in Portugal between September 2014 and December 2019. The sequences obtained from drug resistance testing were used for subtyping, TDR determination, and transmission cluster (TC) analyses.ResultsIn Portugal, the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
2
2
1
Order By: Relevance
“…We also found that, for subtype B, the age at resistance test was associated with being in cluster, with a higher probability among individuals with younger age. This is in accordance with some other studies (18,25). Migration status was also associated with being in clusters: migrants infected with subtype B were mainly in a cluster, and migrants infected with subtype G were less likely to be in a cluster.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that, for subtype B, the age at resistance test was associated with being in cluster, with a higher probability among individuals with younger age. This is in accordance with some other studies (18,25). Migration status was also associated with being in clusters: migrants infected with subtype B were mainly in a cluster, and migrants infected with subtype G were less likely to be in a cluster.…”
Section: Discussionsupporting
confidence: 94%
“…The detection of SDRMs in the present study was consistent with other recent studies published in Europe [ 6 , 7 , 8 ], making our findings one of the more up-to-date studies including the surveillance of resistance to INSTIs. The rate of SDRMs conferring resistance to NRTIs remained stable and similar to a previous study conducted in Portugal [ 7 ]. Interestingly, M184V continues to be transmitted at a very low proportion, with most SDRMs being transmitted as singletons.…”
Section: Discussionsupporting
confidence: 93%
“…Upon identification of a DRM, ART regimens are usually modified accordingly, replacing ineffective drugs with those that are expected to effectively suppress the viral replication [ 5 ]. The European multi-center cohort study conducted in the past 10 years and the Portuguese HIV drug resistance (HIVDR) study conducted in 2021 showed that the prevalence of HIV resistance increased over time [ 6 , 7 , 8 ]. Based on this evidence, the World Health Organization (WHO) stated that further investigation on this subject is necessary in this era of a global scale-up of ART to achieve the 95-95-95 targets [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In subtypes A and B, there were differences concerning age, recentness of infection, and viral load. In subtypes A and B, younger individuals were associated with being NLPs inside clusters, and this is in accordance with other studies associating younger age with clustering [22,27]. Furthermore, in subtype B, the LPs inside clusters were older (more than 31 y/o), with a higher and growing proportion of LPs in clusters as age increased.…”
Section: Discussionsupporting
confidence: 90%